Total systems design MDi (Micro-D International) - Alsua, Agnes Eliza; Lugue, Tess Marichie; Macalinao, Laura Karen Grace; Ponferrada, Regidor (Diliman, Quezon City College of Engineering, 2003)
Micro-D International aspires to be the preferred information and communication technology and eCommerce solutions provider in the country. The corporation has been operating for fifteen years, which is significantly more senior than most of its competitors. However, Micro-D International fails to take advantage of its experience as some traces of MDi's past as a purely distributing firm is causing detriment to MDi's operation as a solutions provider. The organizational structure should be streamlined to reduce costs. They are spending too much on corporate support functions especially on accounting and inventory control. The corporation also needs to establish a position of chief operating officer that will aid the president in solving the communication problems form the different departments. MDi should also shift to the Just-In-Time system and reduce their inventory levels. Logistics functions should be outsourced and the company should now eliminate the need to maintain a warehouse. Also, the accounting system should also be enhanced as it fails to respond to the needs of the whole business. Most of the manual documentation should be integrated into the new software. The company should also strive to increase its sales by investing on market research and aggressive advertising. Market research will help the company in adapting to the ever-changing needs of the information and communication technology market and aggressive advertising will greatly complement this undertaking.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: Micro-D International Inc; Electronic commerce; System design